2006
DOI: 10.1213/01.ane.0000196521.62806.43
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam Attenuates Phenylephrine-Induced Contractions in Rat Aorta

Abstract: In this in vitro study we examined the effects of diazepam on a phenylephrine-induced contraction in rat aorta and determined the associated cellular mechanism focusing on the endothelium-derived vasodilators. The concentration-response curves for phenylephrine and potassium chloride were generated in the presence or absence of diazepam. Phenylephrine concentration-response curves were generated from the endothelium-intact rings pretreated independently with N(W)-nitro-L-arginine methyl ester, PK 11195, tetrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
3
9
1
Order By: Relevance
“…A low-molecular-weight superoxide anion scavenger tiron abolished the indigo carmine-induced potentiation of contraction evoked by phenylephrine. These results, along with previous reports [6,7,[11][12][13], suggest that indigo carmine enhances the phenylephrine-induced contraction in the endothelium-intact rings via NO inactivation induced by indigo carmine-induced ROS production (Fig. 6).…”
Section: Indigo Carmine and Nitric Oxidesupporting
confidence: 88%
See 1 more Smart Citation
“…A low-molecular-weight superoxide anion scavenger tiron abolished the indigo carmine-induced potentiation of contraction evoked by phenylephrine. These results, along with previous reports [6,7,[11][12][13], suggest that indigo carmine enhances the phenylephrine-induced contraction in the endothelium-intact rings via NO inactivation induced by indigo carmine-induced ROS production (Fig. 6).…”
Section: Indigo Carmine and Nitric Oxidesupporting
confidence: 88%
“…Enhanced production of O 2 • -increases NO inactivation [11], which leads to a decrease in endotheliumdependent NO-mediated relaxation. Endothelial NO was reported to inhibit the contractile agonist (e.g., phenylephrine and norepinephrine)-induced contraction of the rat aorta [12,13]. A low-molecular-weight superoxide anion scavenger tiron abolished the indigo carmine-induced potentiation of contraction evoked by phenylephrine.…”
Section: Indigo Carmine and Nitric Oxidementioning
confidence: 98%
“…For example, the BDZ diazepam induces an endothelium-dependent vasodilation involving endothelial NO production in rodents. 18,19 In contrast, our results excluded NO involvement in the mechanism of the BDZ midazolam because the NOS inhibitor NGnitro-L-arginine methyl ester did not modify midazolam-induced vasodilation (Figure 3b). …”
Section: Discussioncontrasting
confidence: 55%
“…In pilot experiments in which aortic rings were exposed to increasing doses of diazepam, we found a vasodilatory response that was comparable to that of midazolam (data not shown). In addition, other authors reported vasodilation induced by different BDZs, such as diazepam in rat aorta, 18,19 canine arteries, 9 and human umbilical arteries and veins; 4 tetrazepam in aorta and portal vein of rats; 10 flurazepam in canine arteries; 9 and clonazepam in human umbilical arteries. 4 Moreover, BDZs seem to have a generalized muscle relaxant effect as demonstrated by diazepam-and clonazepam-induced relaxation of uterine rings from rats 38 and by diazepam-and flurazepaminduced relaxation of isolated taenia coli and longitudinal muscle of guinea pigs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation